Pengaruh Kepemimpinan Komunikasi Organisasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Aceh Singkil - Khairani, Mutiara Malshara (Universitas Muhammadiyah Sumatera Utara, 2025)
Leadership is one of the main factors that determine employee performance in an organization. Effective leadership not only acts as a director who gives instructions, but also encourages employee dedication. Organizational communication also plays an equally important role in improving employee performance. Effective communication can strengthen coordination between employees, reduce misunderstandings, and accelerate the completion of existing tasks. The Secretariat of the Aceh Singkil Regency DPRD is responsible for administrative and operational efficiency, but faces internal challenges such as leadership, communication, and organizational culture that have an impact on employee productivity. This study uses a quantitative approach. The subjects of this study consisted of 43 employees of the Aceh Singkil Regency People's Representative Council Secretariat office. Data collection techniques used observation and questionnaires. Data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear analysis tests, and hypothesis tests. The results of this study indicate that there is a significant influence between leadership, organizational communication and organizational culture on the performance of Aceh Singkil Regency DPRD Secretariat employees. Based on the results of the determination test, the determination coefficient is 0.877. This value shows that the variables of leadership, organizational communication, and organizational culture explain the variation of employee performance variables by 87.7% and the remaining 12.3% is explained by other variables outside the study.